Analisis Penerapan Model Pembelajaran Berbasis Proyek Terhadap Motivasi Belajar Siswa Dalam Penggunaan Teknologi - Syahrul Amrin; Ali Sadikin Ritonga (Jurnal Zeniusi, 2024)
This research explores the effectiveness of the Problem-Based Learning (PBL) model integrated with technology in enhancing student learning motivation. PBL is an instructional approach that places students at the center of the learning process, where they are confronted with real problems that require solutions. In this study, qualitative methods were used to analyze descriptive data in the form of oral and written information as well as observed behavior. The research results show that the integration of technology in PBL provides various significant benefits. Technology enables broad and rapid access to information, making learning more interactive and engaging, as well as facilitating effective collaboration and communication. Additionally, technology allows for quick and personalized feedback, self-directed learning, and individual adjustments according to students' pace and learning styles. The use of gamification elements in learning has also been proven to enhance students' intrinsic motivation. Overall, the integration of technology in Project-Based Learning (PBL) has a positive impact on students' learning motivation, as well as improving critical, creative, and collaborative thinking skills. This research emphasizes that the effectiveness of technology as a supportive tool greatly depends on its use in the appropriate and directed learning context. This finding highlights the importance of implementing PBL integrated with technology to enhance the quality of education in the digital age, as well as to prepare students with the 21st-century skills needed to face global challenges.